KEMAMPUAN PENALARAN KUANTITATIF SISWA DALAM MATERI ALJABAR DI SEKOLAH MENENGAH ATAS - Zalinin, Zalinin; Sugiatno, Sugiatno; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to describe the quantitative reasoning abilities of students in algebraic material in Middle School based on students' mathematical abilities. The research method used was descriptive method with the form of survey study. The subjects of this study were 3 students in class XII Pontianak 2 Public High School. The results of the quantitative reasoning ability test show that the students' quantitative reasoning abilities in algebraic material can be categorized as low. The ability to reverse the calculation process can only be achieved by students who have a high level of mathematical abilities, but the ability to simplify the calculation process can be achieved by most of all students both at high medium and low ability levels. Keywords: Quantitative reasoning, Algebra.